IMPLEMENTASI MODEL COOPERATIVE LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPAS PADA SISWA KELAS V SDN 187 PEKANBARU - Amiratul Fatina; Neni Hermita; Mahmud Alpusari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is a classroom action research (CAR) that aims to improve the activity and learning outcomes of science through the application of the Cooperative Learning model in fifth-grade students of SDN 187 Pekanbaru. The research subjects were 38 students. The research was conducted in two cycles, where each cycle included the planning stage, action implementation, observation, and reflection. Data collection techniques were carried out through observation of student activities and science learning outcome tests. Student activity data were analyzed using percentages, while learning outcome data were analyzed by comparing the increase in scores in each cycle. The results showed that the application of the Cooperative Learning model can improve students' activities and learning outcomes of science. Student activity in cycle I meeting 1 reached 70.83% with a sufficient category, then increased to 87.5% with a good category in cycle I meeting 2, and again increased to 91.67% with a very good category in cycle II meeting 1. In line with the increase in student activity, the results of learning science also increased, namely by 12,77% in cycle I meeting 1 and increased in cycle I meeting 2 to 36.21% and increased again in cycle II meeting 1 from the basic score, with the total student score reaching 3345 with a percentage of 39.35%. Thus, it can be concluded that the Cooperative Learning model in increasing the activity and results of learning science of class V students of SDN 187 Pekanbaru.